Магістральні орієнтири викладання вільної боротьби у закладах вищої освіти - Христова, Тетяна Євгенівна; Абуллаєв, Алтай Карам огли; Ребар, Інесса Василівна; Нестеров, Олексій Сергійович; Грдзелідзе, Сергій Ріпатович (Громадська наукова організація "Всеукраїнська асамблея докторів наук з державного управління", 2023)
Стаття розкриває стратегічні лінії вдосконалення й оновлення методики викладання вільної боротьби в закладах вищої освіти. Відзначено, що в турбулентні часи модернізації освіти підготовка борців у виші неможлива без одного з найважливіших її компонентів - методики початкового навчання. Різним аспектам цієї проблеми присвячено досить багато наукових розвідок, згідно яких методика й організація навчально-тренувального процесу повинні вдосконалюватися на основі досліджень змагальної діяльності та спортивної майстерності, за принципом первинності змагань і вторинності тренування. Мета статті – визначити та обґрунтувати актуальні методичні підходи, які використовуються при викладанні вільної боротьби у закладах вищої освіти. На основі узагальненого структурно-логічного аналізу літературних джерел та власного досвіду доведено, що вдосконалення та оновлення методичних підходів до викладання вільної боротьби у закладах вищої освіти є нагальною потребою сьогодення, адже наявна система є малоефективною. Наголошується, що загальнопедагогічні принципи (зростаючого навантаження, безперервності, свідомості, систематичності, наочності, доступності, індивідуалізації, міцності) поширюються на всі сторони та завдання тренування, визначають зміст, засоби, методи й організацію навчально-тренувального процесу з вільної боротьби у виші. Змістовний компонент та спрямованість початкової підготовки до занять вільною боротьбою повинні відповідати віку, етапу тренування, рівню підготовленості здобувачів вищої освіти. Систематизований аналіз дослідження змагальної діяльності борців показує необхідність первісного вивчення профілюючих елементів боротьби, оскільки вони складають основу ведення боротьби в поєдинку. Визначено, що магістральними орієнтирами викладання вільної боротьби у закладах вищої освіти є дотримання загальнопедагогічних принципів навчання, відповідність навантаження етапу тренування, віку та рівню фізичної підготовленості здобувачів вищої освіти.

The article reveals the strategic lines of improvement and renewal of the methods of teaching freestyle wrestling in higher education institutions. It is noted that, in the turbulent times of modernization of education, the training of wrestlers in higher education is impossible without one of its most important components: the methodology of initial training. Much scientific research has been devoted to various aspects of this problem, according to which the methodology and organization of the educational and training process should be improved on the basis of research on competitive activity and sportsmanship, on the principle of the primacy of competition and the secondary nature of training. The purpose of the article is to identify and substantiate the current methodological approaches used in teaching freestyle wrestling in higher education institutions. Based on a generalized structural and logical analysis of the literature and their own experience, it is proven that improving and updating methodological approaches to teaching freestyle wrestling in higher education institutions is an urgent need of the present, as the existing system is ineffective. It is emphasized that the general pedagogical principles (increasing load, continuity, consciousness, systematics, visibility, accessibility, individualization, strength) apply to all aspects and tasks of training, determining the content, means, methods, and organization of the educational and training process in freestyle wrestling at a university. The content component and orientation of the initial training for freestyle wrestling should correspond to the age, stage of training, and level of preparedness of higher education students. A systematic analysis of the study of wrestlers' competitive activity shows the need for an initial study of the profiling elements of wrestling, as they form the basis of wrestling in a match. It has been determined that the main guidelines for teaching freestyle wrestling in higher education institutions are compliance with the general pedagogical principles of teaching, and compliance of the load with the stage of training, age, and level of physical fitness of higher education students.
Major guidelines for teaching freestyle wrestling in higher education institutions
Keywords: методика навчання; педагогічні принципи; заклади вищої освіти; вільна боротьба; teaching methods; pedagogical principles; higher education institutions; freestyle wrestling